2012
DOI: 10.1007/s12192-011-0296-0
|View full text |Cite
|
Sign up to set email alerts
|

Heterooligomeric complexes of human small heat shock proteins

Abstract: Oligomeric association of human small heat shock proteins HspB1, HspB5, HspB6 and HspB8 was analyzed by means of size-exclusion chromatography, analytical ultracentrifugation and chemical cross-linking. Wild-type HspB1 and Cys mutants of HspB5, HspB6 and HspB8 containing a single Cys residue in position homologous to that of Cys137 of human HspB1 were able to generate heterodimers cross-linked by disulfide bond. Cross-linked heterodimers between HspB1/HspB5, HspB1/ HspB6 and HspB5/HspB6 were easily produced up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
91
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(98 citation statements)
references
References 59 publications
7
91
0
Order By: Relevance
“…Combining NMR, ion-mobility native mass spectrometry, and EM, structural models of the most abundant oligomeric states (24-, 26-, and 28-mers) and a model for the conversion between them have been proposed, providing a deeper understanding of the polydispersity and dynamics of sHsp structures (Baldwin et al 2011b). Further increasing possible complexity, it has been found that various human sHsps may form mixed heterooligomers (Mymrikov et al 2012). The stable protein complexes formed between sHsp and substrate proteins also appear to be polydisperse (Stengel et al 2010), with complexes of pea Hsp18.1 and substrate protein luciferase comprised of variable numbers of both sHsp and substrate protein, covering over 300 different stoichiometries.…”
Section: Introductionmentioning
confidence: 99%
“…Combining NMR, ion-mobility native mass spectrometry, and EM, structural models of the most abundant oligomeric states (24-, 26-, and 28-mers) and a model for the conversion between them have been proposed, providing a deeper understanding of the polydispersity and dynamics of sHsp structures (Baldwin et al 2011b). Further increasing possible complexity, it has been found that various human sHsps may form mixed heterooligomers (Mymrikov et al 2012). The stable protein complexes formed between sHsp and substrate proteins also appear to be polydisperse (Stengel et al 2010), with complexes of pea Hsp18.1 and substrate protein luciferase comprised of variable numbers of both sHsp and substrate protein, covering over 300 different stoichiometries.…”
Section: Introductionmentioning
confidence: 99%
“…This complex was formed only if the mixture of two proteins was preincubated at an elevated temperature (Fig. 4a-c) (Mymrikov et al 2012;Datskevich et al 2012a). We measured the area of the peak of the wild-type HspB6 in the absence and in the presence of the wild-type HspB5 and, by this means, tried to estimate the approximate stoichiometry of the complex formed by these two proteins.…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that the sHsp are able to form heterooligomers (Mymrikov et al 2012;Datskevich et al 2012a;Arrigo 2013). Therefore, it seems reasonable to analyze the effect of the yellow fluorescent protein attached to the C-terminal end of HspB6 on its ability to interact with the wild-type HspB1 and HspB5.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations